Morphological and Molecular Identification of Nematode Parasite Eustrongylides sp. Isolated from Channa punctatus: A Preliminary Study (Journal of the Bangladesh Agricultural University, 2020)
Eustrongylides sp. is considered as a freshwater zoonotic nematode which uses birds as final hosts and other vertebrates (fish, amphibians and reptiles) as intermediate hosts. In this study, a total of 200 specimens of Channa punctatus were collected from different fish markets of Mymensingh city to identify Eustrongylides sp. with determining prevalence, mean intensity and abundance of this species using morphological and molecular tools. Larvae of Eustrongylides sp. were recovered from the abdominal cavity, musculature and ovaries of 101 C. punctatus specimens. Light microscopy (LM) was conducted to observe the surface anatomy of the worm. The worm was slender, elongated and cylindrical, medium to large in size and sometimes broader in the middle portion. The mouth was slit-like, surrounded by two lateral rows of somatic papillae, cephalic end was conical with 12 labial papillae arranged in two circles of 6 papillae each. Oesophagus was leaded into highly coiled intestine and was fairly long, without posterior bulb and posterior extremity with spike like tail process. The parasitological investigations revealed that the prevalence, mean intensity and abundance of Eustrongylides sp. Infestations were 50.5%, 2.06 and 1.04, respectively and varied depend on the size of fish and difference of fish markets. The number of nematodes per fish was ranged from 1 to 13. The prevalence of Eustrongylides sp. also varied from 26.0% to 61.32% in different fish markets and 26.0% to 59.82% in different sizes of the hosts. Eustrongylides sp. was also confirmed by amplifying ITS gene. This is the first report on the identification of larval stage of Eustrongylides sp. from C. punctatus in Bangladesh which provides basic information for further detailed epidemiological and molecular study.J Bangladesh Agril Univ 18(3): 760–767, 2020https://doi.org/10.5455/JBAU.113219